A decade of triage with the Manchester Triage System-The MTS big data study - Ingo Gräff; Moritz Berger; Matthias Schmid; Monika Kogej (PLoS ONE, 2026)
Background Over the past 25 years, numerous studies have evaluated triage system performance, but longitudinal data are limited. This study is the first to assess the Manchester Triage System (MTS) over a decade to determine the accuracy of initial patient assessments and system stability under external influences such as staff turnover, health policy changes, demographic shifts, and the COVID-19 pandemic. Methods We conducted a large-scale, monocentric, retrospective observational study at a tertiary care hospital. Results Between 2014 and 2023 a total of 355,135 emergency patients were included. Average age increased from 48.1 to 52.1 years. The distribution of the five MTS urgency levels remained stable. Prediction of hospital admission (AUC 0.719–0.756) and ICU admission (AUC 0.831–0.862) was consistent throughout the period. Twelve-hour survival probabilities were above 0.99 for “blue” to “orange” patients and above 0.89 for “red” patients. Short-term mortality prediction (AUC) ranged from 0.845 to 0.894. Thirty-day survival remained >0.8 for “blue” to “orange” stages, while the “red” stage declined from 0.63 (2014) to 0.44 (2023). The AUC for 30-day mortality increased from 0.672 to 0.750 over the decade. Conclusion Construct validity assessment demonstrates that the MTS reliably assigns appropriate urgency levels to incoming emergency patients. Longitudinal evaluation shows that its accuracy remained stable over ten years despite high staff turnover, health policy and demographic changes, and the COVID-19 pandemic. These findings confirm the robustness and reliability of the MTS in a high-volume tertiary care setting and support its continued use for emergency patient prioritization.